MÉTODOS DE APLICAÇÃO DE BIOINSUMO DE MICROALGA EM HORTALIÇAS - SILVA, Gabriel Martins; SANT’ANA, Gabriela Rodrigues; VENDRUSCOLO, Eduardo Pradi; DE PIERI, Kamille Rodrigues; ARAUJO, Tassila do Nascimento (ANAIS DO ENIC, 2026)
.